1934
DOI: 10.1098/rspa.1934.0212
|View full text |Cite
|
Sign up to set email alerts
|

The swelling of charcoal. Part III. Experiments with the lower alcohols

Abstract: When a rod of well-baked wood charcoal contained in an extensometer is plunged into methyl alcohol, a noise like the quenching of hot iron is produced, and the moving parts of the extensometer are violently disturbed, as by a sudden impact. Though such effects are to be classed as irreversible and even irreproducible (where the charcoal is visibly fractured), quantitative investigation shows the expansion phenomenon to be no more inherently so than are the effects which accompany the admission of gas to an eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1939
1939
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Based on a series of experiments, [71][72][73][74] which all showed monotonic expansion of charcoal samples with increased adsorbate pressure, Bangham concluded that the measured linear strain is proportional to the decrease in the surface energy c of a solid, caused by adsorption…”
Section: Monotonic Expansion: Bangham's Lawmentioning
confidence: 99%
“…Based on a series of experiments, [71][72][73][74] which all showed monotonic expansion of charcoal samples with increased adsorbate pressure, Bangham concluded that the measured linear strain is proportional to the decrease in the surface energy c of a solid, caused by adsorption…”
Section: Monotonic Expansion: Bangham's Lawmentioning
confidence: 99%
“…In this work we focus on the origin of adsorption-induced deformation of microporous carbons. Typically microporous materials, such as carbons or zeolites, exhibit a nonmonotonic adsorption-induced deformation: they contract at low stages of micropore filling and switch to expansion as adsorption progresses. The extent of observed contraction and expansion depends on the structure of the adsorbent, , the adsorptive applied, ,,, and the temperature. ,,, The first model for adsorption-induced deformation of microporous materials was proposed by Bangham, who considered the energy change of the adsorbate–adsorbent interface to be the sole source of stress within the porous structure . This concept was later implemented into the framework of Biot’s poromechanics by the use of the Gibbs adsorption equation. ,, However, the fundamental issue of this approach is that adsorption leads to a reduction of the interfacial energy, and thereby only expansion should be observed, in clear contradiction with experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…An early experimental investigation by Meehan in 1927 reported the expansion of charcoal on adsorption of carbon dioxide . Later the expansion of charcoal upon exposure to water vapor, ammonia, alcohols, and other gases was studied by Bangham and co-workers, and the deformation of carbon rods was investigated by Flood and co-workers in the 50s and 60s, who found evidence of contraction at low pressures. Adsorption-induced deformation was also investigated for materials other than carbon, and both expansion and contraction were recorded.…”
Section: Introductionmentioning
confidence: 99%